2023
DOI: 10.3390/plants12020409
|View full text |Cite
|
Sign up to set email alerts
|

Auxin Transporter OsPIN1b, a Novel Regulator of Leaf Inclination in Rice (Oryza sativa L.)

Abstract: Leaf inclination is one of the most important components of the ideal architecture, which effects yield gain. Leaf inclination was shown that is mainly regulated by brassinosteroid (BR) and auxin signaling. Here, we reveal a novel regulator of leaf inclination, auxin transporter OsPIN1b. Two CRISPR-Cas9 homozygous mutants, ospin1b-1 and ospin1b-2, with smaller leaf inclination compared to the wild-type, Nipponbare (WT/NIP), while overexpression lines, OE-OsPIN1b-1 and OE-OsPIN1b-2 have opposite phenotype. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Specifically, we found SAUR10, SAUR28, SAUR63, and SAUR68 to be highly upregulated. SAUR10 has been shown to increase growth when overexpressed in Arabidopsis 30 , and was recently shown to be essential for normal growth and yield in rice 31 . SAUR28, along with three other nearby SAUR genes, was identified as the largest effect QTL for leaf architecture changes at bolting stage in response to different temperatures 32 .…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, we found SAUR10, SAUR28, SAUR63, and SAUR68 to be highly upregulated. SAUR10 has been shown to increase growth when overexpressed in Arabidopsis 30 , and was recently shown to be essential for normal growth and yield in rice 31 . SAUR28, along with three other nearby SAUR genes, was identified as the largest effect QTL for leaf architecture changes at bolting stage in response to different temperatures 32 .…”
Section: Resultsmentioning
confidence: 99%
“…Rice japonica variety Nipponbare and ospin1b mutants [58] were employed for the experiments. Rice plants were cultured using hydroponic systems according to our previous report [24]. In brief, after sterilization, rice seeds were incubated in Petri dishes with wetted filter papers at 28-30 • C for several days in the dark.…”
Section: Plant Materials and Abiotic Stress Treatmentsmentioning
confidence: 99%
“…By contrast, the mutation of OsPIN1b by CRISPR/Cas9 technology causes no obvious phenotype in rice, only ospin1a ospin1b double mutants show pleiotropic phenotypes [23]. Recently, Zhang et al reported that OsPIN1b participates in regulating leaf inclination in rice [24]. Additionally, nutrient supply influences OsPIN1b expression; for example, sufficient nitrate conditions significantly induce OsPIN1b expression [25], whereas low-nitrogen and -phosphate conditions significantly down-regulate OsPIN1b expression.…”
Section: Introductionmentioning
confidence: 99%
“…The first is to detect ramps from a time series of wind power or wind speed forecasts according to a given ramp-event definition [37]. The second strategy is to use regression to predict ramp-events from historical data [38], [39]. According to [38], the ramp capture rate was less than 50% for most cases.…”
Section: B Brief Review Of Ramp Prediction Approachesmentioning
confidence: 99%